2022
DOI: 10.1101/2022.06.09.22276199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Road environment characteristics and fatal crash injury during the rush hour period in the U.S.: Model testing and nested analytical study

Abstract: Background: A substantial proportion of crash injuries occur during the rush hour period. This study aims to assess the relationship between county level road environmental characteristics and fatal road crash counts during the rush hour period. Method: We merged eight-year (2010 to 2017) data from the Fatality Analysis Reporting System. We limited the data to crashes during the rush hour period (6 to 9 am; 3 to 7 pm). The outcome variable was the counts of fatal crashes per county. The predictor variables we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…This observed finding may suggest the disproportionate distribution of non-geriatric road users in metropolitan urban areas and the impact of risky driving behaviors associated with young and middleaged drivers. Earlier studies have reported that non-geriatric road users are more likely to drive while under the influence of drugs and alcohol, 9,55,56 and engage in phone-related distracted driving. [57][58][59][60] These unique characteristics may account for the observed elevated fatal crash rate ratio in nongeriatric road users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observed finding may suggest the disproportionate distribution of non-geriatric road users in metropolitan urban areas and the impact of risky driving behaviors associated with young and middleaged drivers. Earlier studies have reported that non-geriatric road users are more likely to drive while under the influence of drugs and alcohol, 9,55,56 and engage in phone-related distracted driving. [57][58][59][60] These unique characteristics may account for the observed elevated fatal crash rate ratio in nongeriatric road users.…”
Section: Discussionmentioning
confidence: 99%
“…Poverty, an exemplar of economic stability, predicts substance use, injury, and adverse events from chronic diseases. 4 Similarly, rurality, an exemplar of neighborhood and built environment is associated with increased hospital closure, [5][6][7] longer emergency medical service response and hospital transit time, [8][9][10][11] , and increased deaths without resuscitation. 10 Understanding the relationship between SDoH and fatal crash counts will further highlight the importance of improving measures of SDoH.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have reported increased speeding behavior among road users in rural areas [74] and non-use of seat belts among older adult drivers [75]. Rural areas also experience significantly prolonged response times [24,26], increased deaths at the crash scene [26], and increased proportions of crash fatalities [76][77][78]. Additionally, the impact of hospital closures in rural areas may further explain the rural-urban disparity in crash outcomes since hospital closures is directly linked with reduced availaibility of healthcare professionals and reduced access to healthcare [79][80][81][82].…”
Section: Plos Onementioning
confidence: 99%